Community Empowerment in the Landscaping of Gardens around Karo Traditional Houses to Support Cultural Ecotourism in Lingga Village - Mei Brilian Harefa; Dasrizal; Nurul Adha Sitorus; Egy Bremana Ginting; Junianty Dahnita Br Purba (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
Lingga Village in Karo Regency, North Sumatra, is a cultural village that preserves the traditional architecture of the Karo people, particularly the Siwaluh Jabu traditional house, which reflects the community’s life philosophy, social order, and spirituality. The surrounding environment of these traditional houses remains poorly organized, with vacant land left unmanaged and declining awareness of cultural preservation, resulting in suboptimal utilization of the area’s aesthetic value, cultural function, and tourism potential. This community service program aims to arrange a cultural garden around the traditional houses while empowering the local community to manage the cultural landscape in a sustainable manner, with a focus on preserving cultural identity, improving environmental quality, and strengthening the local economy through the development of cultural tourism and agrotourism. The implementation method adopts a community-based participatory approach, carried out through several stages: site observation and mapping, focus group discussions, planning and designing the cultural garden, training and knowledge transfer, collective implementation of garden arrangement, as well as evaluation and documentation. The garden design integrates the orientation of the Siwaluh Jabu house, the cosmological meaning of space, ecological landscape principles, and the selection of local vegetation with symbolic, aesthetic, and economic value, organized into aesthetic, educational, and productive zones. The results of the program indicate the establishment of a well-arranged cultural garden rich in Karo cultural symbols, increased community capacity and participation, and the creation of a sustainable cultural landscape management model that functions as a “living laboratory” combining aesthetic, educational, economic, and spiritual roles. This model positions the community as the main actor and holds potential to be replicated in other cultural villages with similar characteristics.